Rac1 GTPase is a critical factor in phagocytosis in the large yellow croaker Larimichthys crocea by interacting with tropomyosin. Issue 91 (August 2019) - Han, Fang; Li, Wanbo; Liu, Xiande; Zhang, Dongling; Liu, Lanping; Wang, Zhiyong
Abstract: The Rho family GTPase Rac1 acts as a molecular switch for signal transduction to regulate various cellular functions. Here, a Rac1 homolog (LcRac1) was identified in large yellow croaker ( Larimichthys crocea), one of the most economically important marine fishes. The LcRac1 protein was expressed in Escherichia coli and purified. Subsequently the specific antibody was raised using the purified fusion protein (GST-LcRac1). LcRac1 was ubiquitously expressed in all 12 tissues we examined, with the highest expression in heart and blood and the weakest expression in head-kidney and spleen. Moreover, time course analysis revealed that LcRac1 expression was obviously up-regulated in liver, spleen and head-kidney after immunization with Poly I:C, LPS and Vibrio parahemolyticus . On the other hand, on the basis of protein interaction, it was found that the LcRac1 interacted with Tropomyosin, a crucial protein in the process of phagocytosis. Furthermore, RNAi assays indicated that the phagocytic percentage and phagocytic index were significantly decreased when the LcRac1 gene was silenced by sequence-specific siRNA. Fluorescence microscopy assays revealed FITC-labeled V. parahemolyticus were remarkably decreased after LcRac1 was silenced by sequence-specific siRNA at 24 h. These findings implicate the vital role of LcRac1 in innate immunity in the large yellow croaker. Highlights: A Rho family GTPase Rac1 (LcRac1) was cloned from large yellow croaker and the protein was expressed in E. coli and purified. LcRac1 mRNA and protein were significantly up-regulated following Poly I:C, LPS and Vibrio parahemolyticus stimulation. It was found that the LcRac1 interacted with tropomyosin, a crucial protein in the process of phagocytosis. The phagocytic percentage and phagocytic index were significantly decreased when the LcRac1 gene was silenced by siRNA. Rac1 GTPase might be involved in the phagocytotic pathway through the interaction with tropomyosin.